RETENSI BAHAN PENGAWET EKSTRAK DAUN TEMBELEKAN (Lantana camara L) PADA BEBERAPA JENIS KAYU DAN EFEKTIFITASNYA TERHADAP SERANGAN RAYAP TANAH (Coptotermes sp.) - Riska, Riska; Erniwati, Erniwati; Hapid, Abdul (Warta Rimba, 2014)
High-grade durable wood could not be longer to meet the various needs, this caused by limited and the more expensive price, so it must use low grade durable wood. The use of low grade durable wood should be followed by the wood preservation process. This study aims to determine the preservative retention of leaves tembelekan (Lantana camara L) on bayur (Pterospermum sp), benuang (Octomeles sumatrana Miq) and durian (Durio zibethinzs) and its effectiveness against subterranean termites (Coptotermes sp), attack. It was conducted at the Laboratory of Agrotechnology, Faculty of Agriculture, University Tadulako in March to june 2014. Testing Subterranean termites (Coptotermes sp) test was carried out at the Maku Village, District of Dolo, Sigi Regency, Central Sulawesi, using a completely randomized design (CRD), with treatment of different wood species and 3 days soaking duration at a concentration of 1% preservative with 6 replications. The results show the moisture content of bayur, benuang and durian woods are 13,10%, 10,81% and 11,35% respectively. The wood densiy of bayur 0,480g/cm3, benuang 0,277 g/cm3 and durian 0,402g/cm3 and the highest retention values is found at wood of durian 59,09 g/cm3 and the highest retention values is at bayur 41,67 g/cm3. In addition, the highest weeight loss (leas effectiveness) of 15,02% on the wood of bayur (control) and the lowest (highest Effectiveness) on wood of benuang 0,72%. Key words: Leaf extract of tembelekan, Lantana camara L, Octomeles sumatrana Miq, Pterospermum sp, durio sibethinzs